Cancer Immunotherapy of TLR4 Agonist–Antigen Constructs Enhanced with Pathogen‐Mimicking Magnetite Nanoparticles and Checkpoint Blockade of PD‐L1. Issue 4 (20th December 2018) - Traini, Giordano; Ruiz‐de‐Angulo, Ane; Blanco‐Canosa, Juan Bautista; Zamacola Bascarán, Kepa; Molinaro, Antonio; Silipo, Alba; Escors, David; Mareque‐Rivas, Juan C.
Abstract: Despite the tremendous potential of Toll‐like receptor 4 (TLR4) agonists in vaccines, their efficacy as monotherapy to treat cancer has been limited. Only some lipopolysaccharides (LPS) isolated from particular bacterial strains or structures like monophosphoryl lipid A (MPLA) derived from lipooligosaccharide (LOS), avoid toxic overactivation of innate immune responses while retaining adequate immunogenicity to act as adjuvants. Here, different LOS structures are incorporated into nanoparticle‐filled phospholipid micelles for efficient vaccine delivery and more potent cancer immunotherapy. The structurally unique LOS of the plant pathogen Xcc is incorporated into phospholipid micelles encapsulating iron oxide nanoparticles, producing stable pathogen‐mimicking nanostructures suitable for targeting antigen presenting cells in the lymph nodes. The antigen is conjugated via a hydrazone bond, enabling rapid, easy‐to‐monitor and high‐yield antigen ligation at low concentrations. The protective effect of these constructs is investigated against a highly aggressive model for tumor immunotherapy. The results show that the nanovaccines lead to a higher‐level antigen‐specific cytotoxic T lymphocyte (CTL) effector and memory responses, which when combined with abrogation of the immunosuppressive programmed death‐ligand 1 (PD‐L1), provide 100% long‐term protection against repeated tumor challenge. This nanovaccine platform in combination with checkpoint inhibition of PD‐L1 represents a promising approach to improve the cancer immunotherapy of TLR4 agonists. Abstract : A cancer vaccine platform based on pathogen‐mimicking Toll‐like receptor (TLR4) agonist‐functionalized magnetite containing nanostructures and chemoselective covalent conjugation of antigen by aniline‐catalyzed hydrazone ligation is designed and developed. Vaccination with these nanovaccines in combination with the abrogation of tumor cell programmed death‐ligand 1 (PD‐L1) expression confers complete protection against multiple melanoma challenges.